Bacteriological analysis of date palm fruits sold in Katsina metropolis - Umar, ZD; Bilkisu, A; Bashir, A (International Journal of Environment, 2014)
Date palm is widely cultivated, distributed and consumed by various individuals. Most of the date palm fruits sold in Nigeria are either damaged or has insufficient quality for human consumption. This study was carried out to determine the bacterial load of date fruits in Katsina metropolis. Enumeration of bacteria was determined using pour plate technique. Serial dilution was carried out, where 10g of date fruits was homogenized in 90ml of diluents and used as stock solution. The bacterial counts were determined using colony forming unit per gram of the date fruit samples (cfu/g). The results obtained revealed high bacterial load in all the samples analyzed, which indicates the fruits contamination with bacteria. This may be due to unhygienic handling of the fruits from the local sellers and the nutritional contents of the fruit that may serve as good source of nutrients to bacteria. Date fruits should be packed and processed in a very hygienic condition for public health importance DOI: http://dx.doi.org/10.3126/ije.v3i2.10517 International Journal of the Environment Vol.3(2) 2014: 83-86